β1-adrenergic Receptor within Nanodiscs of 10-16 nm in Diameter Retains Ligand-binding Properties - Sharf, T.V.; Balobanov, V.A.; Peclo, M.M.; Lipatova, L.N.; Kashirina, N.M.; Kuznetzova, I.B.; Yanushevskaya, E.V.; Rutkevich, P.N.; Rybalkin, I.N.; Kolb, V.A.; Vlasik, T.N.; Efremov, E.E. (Biomedical Chemistry: Research and Methods, 2024)
The detection of autoantibodies against the β1-adrenergic receptor (ADRB1 Ab) in the blood of patients and the monitoring of the levels of these antibodies is an urgent need in clinical practice. The solid-phase enzyme-linked immunosorbent assay (ELISA), using ADRB1 in native conformation as antigen, seems to be the most suitable for this task. We have previously tested various amphipathic polymers for their ability to solubilize ADRB1 in the form of nanodiscs so that ADRB1 retains its antigenic properties. The aim of the present work was to investigate the ligand binding properties of ADRB1 in nanodiscs prepared with amphipathic polymers such as UltrasoluteTM Amphipol (UA17) and AASTY 11-45 and to determine the size of the nanodiscs by dynamic light scattering. The binding of the ligands isoproterenol (agonist) and cyanopindolol (antagonist) was assessed by their ability to compete with recombinant hAB2367 antibodies specific for the second extracellular loop of ADRB1 in ELISA. It was found that ADRB1 solubilized with UA17 and AASTY 11-45 retained its ligand-binding properties. This fact supports the assumption that ADRB1 retains its native structure in nanodiscs. The size of nanodiscs prepared with UA17 was determined for the first time by dynamic light scattering. In the range of polymer concentrations from 0.0625% to 0.5%, no significant differences were observed in the size of the nanodiscs, which varied between 10 and 16 nm.